2012
DOI: 10.1002/ardp.201200219
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antitubercular Activity Evaluation of Novel Unsymmetrical Cyclohexane‐1,2‐diamine Derivatives

Abstract: A library of unsymmetrical cyclohexane-1,2-diamine derivatives were synthesized and evaluated for their activity against Mycobacterium tuberculosis H37Rv in vitro. Out of the 46 compounds synthesized, eight compounds (11h, 13a, 13e, 13f, 14a, 14c, 14d, and 15d) were found to be active at or below 6.25 µM concentration, with negligible toxicity to human red blood cells at a concentration much higher than the MIC(99) . Compound 13a was the best active compound showing inhibition at 3.125-6.25 µM, and was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…7,8 SQ109 is an important drug currently in phase II clinical trial for the treatment of tuberculosis. [9][10][11][12][13] In the attempts to synthesize new antimicrobial agents, [14][15][16] we reported antimicrobial activity of various series of cyclohexane diamine derivatives [17][18][19][20][21] and in continuation with our efforts herein we report the synthesis and antimicrobial activity of another series of novel cyclohexane diamine derivatives (Fig. 1).…”
Section: Introductionmentioning
confidence: 92%
“…7,8 SQ109 is an important drug currently in phase II clinical trial for the treatment of tuberculosis. [9][10][11][12][13] In the attempts to synthesize new antimicrobial agents, [14][15][16] we reported antimicrobial activity of various series of cyclohexane diamine derivatives [17][18][19][20][21] and in continuation with our efforts herein we report the synthesis and antimicrobial activity of another series of novel cyclohexane diamine derivatives (Fig. 1).…”
Section: Introductionmentioning
confidence: 92%
“…Briefly, 20 was formed via heating of 18 in the presence of urea followed by deoxychlorination with POCl 3 . Mono-Boc protected diamines 22a – d , 26a , b , 29 , and 32 , prepared according to known procedures or commercially available, were coupled to 20 using microwave irradiation at 150 °C. Removal of the Boc group was effected either under acidic conditions to yield the bis-TFA salt or via microwave-promoted thermolysis to give the free base.…”
Section: Resultsmentioning
confidence: 99%
“…aeruginosa [6], Mycobacterium tuberculosis [7][8][9], and S. aureus [6,8]. Moreover, it was found that (1S,2S) enantiomers generally have lower minimum inhibitory concentrations compared to racemate [6].…”
Section: Introductionmentioning
confidence: 99%